ANALISIS YURIDIS IMPLEMENTASI KETENTUAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) RUMAH NEGARA DAN MESS - Taswin; Arywarti Marganingsih; Slamet Riyadi (CV. ADIBA AISHA AMIRA, 2026)
The obligation to pay land and building tax for state-owned houses in areas with high rates often becomes an obstacle in the occupancy because residents feel reluctant to pay. This has an impact on declining interest in occupying state-owned houses, resulting in many state-owned houses being unoccupied. This paper is compiled using a legal regulatory approach related to the object of study. The Land and Building Tax Law stipulates that state-owned houses and mess are taxable objects. The Regional Tax and Retribution Law regulates the management of land and building tax under the authority of districts/cities, except for Jakarta, where authority lies at the provincial level. The implementation of the PBB-P2 payment regulation for state-owned houses and mess in each region is highly dependent on the fiscal policy of each regional government. The existence or absence of exemption from the principal land and building tax for state-owned houses and mess in each region is determined by local regional policy. Some regional governments provide official exemption from the principal land and building tax for state-owned houses and mess. This policy is not yet widely known. Due to the differences in policies in each region regarding the principal exemption from land and building tax for state-owned houses, adjustments are needed regarding the clauses on the obligation to pay land and building tax in the regulations on state-owned house occupancy within the Ministry/Institution/Regional Government.